THE MEDIATION EFFECT OF CUSTOMER SATISFACTION IN RELATIONSHIP BETWEEN PRODUCT QUALITY AND SERVICE QUALITY TOWARDS CUSTOMER LOYALTY IN FUZEE SUSHI - Charly Hongdiyanto; Kevin Liemena (FIRM Journal of Management Studies, 2021)
Food and beverage industry in Indonesia has been growing constantly every year and also contributed to manufacture and economy growth in both current and the next following years. The important role of food and beverage industry is transparent through the consistent contribution and significant impact toward Gross Domestic Product and food and beverage startup businesses has been experiencing growth every year due to the growth of population in Indonesia. This study was made to know the effect of product quality and service quality towards customer loyalty of Fuzee Sushi. There is also customer satisfaction as a mediator between product quality and service quality to customer loyalty. This research aims on Fuzee Sushi’ customers that has bought the product more than once. An online questionnaire was distributed to the entire sample and used five points Likert scale as a measurement method. The data are analyzed using Partial Least Square. The result of this research showed that product quality has positive relationship toward customer loyalty directly however, service quality does not have positive impact directly toward customer loyalty. Product quality and service quality mediated by customer satisfaction has positive impact towards customer loyalty. The findings purpose is to understand more about product quality, service quality, customer satisfaction, and customer loyalty relationship in start-up food and beverage business in Indonesia.